2004
DOI: 10.1097/00006216-200407000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interpretive Styles of Stress Resiliency on Registered Nurse Empowerment

Abstract: The purpose of this predictive, nonexperimental study was to describe the influence of 3 interpretive styles of stress resiliency on phychological empowerment; psychological empowerment has been identified as a primary predictor of RN job satisfaction. Subjects were 142 nurses, randomly selected from 4 unit in 2 hospitals in a mid-Atlantic state. Measures used were Spreitzer's questionnaire for psychological empowerment (Chronbach alpha for this study = .89) and Thomas and Tymon's Stress Resiliency Profile for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…Simoni et al . () showed that the self‐resilience of nurses helped with their ability to cope effectively and with their personal control, positive adaptation and personal growth. They found that self‐resilience against stress explained 24% of the psychological empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Simoni et al . () showed that the self‐resilience of nurses helped with their ability to cope effectively and with their personal control, positive adaptation and personal growth. They found that self‐resilience against stress explained 24% of the psychological empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some methodological limitations (addressed in the limitation section) and the low level of evidence, all seven articles (Simoni et al . , Ablett & Jones , Gillespie et al . , , Hodges et al .…”
Section: Problem Identification Stagementioning
confidence: 99%
“…Of the seven studies, three were quantitative (Simoni et al . , Gillespie et al . , ) and four were qualitative (Ablett & Jones , Hodges et al .…”
Section: Problem Identification Stagementioning
confidence: 99%
“…Another method mentioned is to observe good role models, how they interact and maintain their effectiveness both personally and professionally. Nurses who have a sense of agency, believe they are effective and imagine their own success are more likely to feel empowered (Simoni, Larrabee, Birkhimer, Mott & Gladden, 2004). The strategy of creating positive interpretations from previously unhelpful thinking assists with development of self-efficacy (Laschinger et al, 2012).…”
Section: Ways I Ammentioning
confidence: 99%